Fusion of a bacterial cadherin-like domain and green fluorescent protein as a specific probe to study biofilm matrix formation in Rhizobium spp - Abdian, Patricia Lorena; Malori, María Soledad; Caramelo, Julio J.; Maglio Checchi, Abi; Russo, Daniela M.; Zorreguieta, Angeles; Berretta, Marcelo Facundo; Benintende, Graciela Beatriz (Microbiology Society, 2024)
Rhizobium adhering proteins or ‘Raps’ are secreted proteins identified in a very restricted group of rhizobial strains, specifically those belonging to R. leguminosarum and R. etli. The distinctive feature of members of the Rap family is the presence of one or two cadherin-like domains or CHDLs that are also present in numerous extracellular bacterial and archaeal proteins and were proposed to confer carbohydrate binding ability. We have previously made an in-depth characterization of RapA2, a calciumbinding lectin, composed by two CHDLs, involved in biofilm matrix remodelling in R. leguminosarum bv. viciae 3841. In this study, CHDLs derived from RapA2 were analysed in detail, finding significant structural and functional differences despite their considerable sequence similarity. Only the carboxy-terminal CHDL retained properties similar to those displayed by RapA2. Our findings were used to obtain a novel fluorescent probe to study biofilm matrix development by confocal laser scanning microscopy, and also to shed some light on the role of the ubiquitous CHDL domains in bacterial secreted proteins.